2001
DOI: 10.1021/cm0110829
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Optical, and Scanning Tunneling Microscopic Studies on Layer Type CdIn2S4-xSex (1.75 ≤ x ≤ 2.75)

Abstract: The present paper deals with the microstructural parameters calculated from X-ray diffraction data, electrical and optical investigations, and scanning tunneling microscopy (STM) studies on ZnIn 2 S 4 IIIa layer type CdIn 2 S 4-x Se x (1.75 e x e 2.75) quaternary chalcogenides. Microstructural parameters such as dislocation density, root-mean-square strain, stacking fault probability, crystallite size anisotropy, and layer disorder parameters of these compounds have been calculated. The temperature variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Furthermore, it is also observed that peaks are asymmetric at the lower angle than on the higher angle regions. It is well known that such asymmetric behavior of MMT peak in the presence of MWCNT could be attributed to the introduction of layer disorder in MMT . Imperfection of crystallite as a result of lattice strain, dislocation, and stacking faults are also known to contribute toward the broadening of X‐ray diffraction peak of MMT/MWCNT.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is also observed that peaks are asymmetric at the lower angle than on the higher angle regions. It is well known that such asymmetric behavior of MMT peak in the presence of MWCNT could be attributed to the introduction of layer disorder in MMT . Imperfection of crystallite as a result of lattice strain, dislocation, and stacking faults are also known to contribute toward the broadening of X‐ray diffraction peak of MMT/MWCNT.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Clay minerals have been extensively used as a reinforcing agent because of their low cost and easy availability 14,19,20 compared to other layered materials. [21][22][23] Especially, naturally occurring sodium montmorillonite (Na + -MMT) has 2:1 layered silicates. The crystal lattice of Na + -MMT consists of a central octahedral sheet of alumina/magnesium sandwiched between two fused tetrahedral sheets.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The degree of improvement of polymeric properties is extremely dependent on the degree of dispersion of aluminosilicate layers in the polymer matrix, i.e., it is directly dependent on the size of the clay particles dispersed; [5] as a result, either intercalated nanocomposites in which the polymer chains are inserted regularly in between the clay layers or delaminated nanocomposites where silicate layers are randomly dispersed in the polymer matrix or partially delaminated nanocomposites where there is the existence of both these configurations may be emerged out. Sodium montmorillonite (Na þ -MMT), an inorganic material with layered structure, [6][7][8] consists of negatively charged silica sheets held together by charge balancing counter ions Na þ . These counter ions in Summary: Ethylene vinyl acetate (EVA) copolymer/dodecyl ammonium ion intercalated montmorillonite (12Me-MMT) nanocomposites were swelled in xylene under atmospheric condition.…”
Section: Introductionmentioning
confidence: 99%